Best Answer

10x + 2y + 8z - 5x + 4z - 4y

= 10x - 5x + 2y - 4y + 8z + 4z

= (10 - 5)x + (2 - 4)y + (8 + 4)z

= 5x - 2y + 12z

Study guides

☆☆

Q: 10x plus 2y plus 8z-5x plus 4z-4y equals?

Write your answer...

Submit

Still have questions?

Related questions

x2 + 10x + 21 = (x + 3)(x + 7)

x + 13x + 10x = 50 - 6

10x + 3 = 15 10x = 15 - 3 10x = 12 x = 1.2

y=-10x-4

5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8

6.28

x=-1.6

10x+7 = 5x+32 10x-5x = 32-7 5x = 25 x = 5

-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1

6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1

53

It is: x = 1.2

People also asked

Featured Questions